Karakteristik Distribusi Temperatur Build Part pada Proses Pressureless Indirect Sintering - Susilo Adi Widyanto; Syaiful . (Jurnal Teknik Mesin (Sinta 3), 2011)
Curling phenomenon on rapid prototyping (RP) product is an actual problem which has not been solved clearly, also on MMD-Is product. Previous experiment showed, it was caused dominantly by un-uniformity of temperature distribution in build part system when sintering was executed. Differ to the sintering process in the common commercial RP process, sintering process in MMD-Is is conducted in supporting powder media. The research is aimed to observe the effect of supporting powder materials, particle size and configuration of heater system on temperature distribution of the build part. Temperature distribution was measured by immersing thermocouples into supporting powder in vertical and horizontal formation. The experimental results show that the un-uniformity of the build part temperature is caused by secondary heating phenomenon by piston material at base position.